Evaluasi Tarif Berdasarkan Biaya Operasional Kendaraan (BOK) dan Load Factor Angkutan Umum Kota Kupang (Studi Kasus: Trayek 2 dan Trayek 6)) - Bauru, Roswita Rambu; Frans, John H.; Sir, Tri M.W. (Universitas Nusa Cendana, 2023)
Public transportation (Bemo) is one of the transportation services that serve the people of Kupang City in a predetermined route, the route that is passed usually has many public facilities. Public transportation is one of the basic needs of the people in Kupang City. But if it is not handled properly, it will become a problem for providers and users of public transportation services. So this study aims to determine tariffs based on Vehicle Operating Costs (BOK), Ability To Pay (ATP), and Willingness To Pay (WTP) of public transport service users in Kupang City, as well as to analyze the ideal tariff based on Ability To Pay (ATP) and Willingness To Pay (WTP) of public transport service users. The public transport routes that will be observed in this study are route 2 and route 6. With the length of route 2 is 10.145 km and the length of Route 6 is 8.573 km. Analysis of Vehicle Operating Costs (BOK) will use the method of Director General of Land Transportation number SK.687/AJ.206/DRJD/2002 concerning technical guidelines for the implementation of public passenger transportation in urban areas on fixed and regular routes. While analyzing the calculation of Ability To Pay (ATP) and Willingness To Pay (WTP) using cross tabulation and travel budged methods. From the results of the analysis it is known that the current tariff in the field is greater than the calculated tariff of Vehicle Operating Costs (BOK) and Willingness To Pay (WTP), but the applicable tariff is smaller than Ability To Pay (ATP). Due to the problem of the pertalite fuel price increase from Rp.7,650 to Rp.10,000, the current tariff increased from Rp.3,000 to Rp.5,000 for the public and Rp.2,000 to Rp.3,500 for students, while from the calculation of the amount of the Vehicle Operating Cost (BOK) tariff is Rp.3,942 for route 2, and Rp.3,483 for route 6. The Willingnes To Pay (WTP) value is Rp.2,222 while the Ability To Pay (ATP) value is greater, namely Rp.8,148.